2019
DOI: 10.1371/journal.pone.0211619
|View full text |Cite
|
Sign up to set email alerts
|

“Even if she’s really sick at home, she will pretend that everything is fine.”: Delays in seeking care and treatment for advanced HIV disease in Kinshasa, Democratic Republic of Congo

Abstract: Introduction HIV prevalence in the Democratic Republic of Congo (DRC) is estimated to be 1.2%, and access to HIV testing and treatment remains low across the country. Despite advances in treatment, HIV continues to be one of the main reasons for hospitalisation and death in low- and middle-income countries, including DRC, but the reasons why people delay seeking health-care when they are extremely sick remain little understood. People in Kinshasa, DRC, continue to present to health-care facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…These disparities in ART use between male and female caregivers in the middle through fifth wealth quintiles were not clear, thus a need for further research to clarify the observed relationship. Overall, other studies have observed higher likelihood of ART use with better economic status [7,14,57,58,69].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These disparities in ART use between male and female caregivers in the middle through fifth wealth quintiles were not clear, thus a need for further research to clarify the observed relationship. Overall, other studies have observed higher likelihood of ART use with better economic status [7,14,57,58,69].…”
Section: Discussionmentioning
confidence: 87%
“…Rural populations have been reported to be more communal than urban populations [56]. This may be one of the likely routes for better social support structures which are key to ART use [7,55,57]. While more studies may be needed to explain the mechanisms through which ART use and rural-urban residences are related, overall, there is a need to tailor interventions to the specific needs of each area [58] to ensure that all PLHIV are on treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, twenty-three studies specifically researching stigma in DR Congo (DRC) have been published. Twenty-one have concentrated on sex-related stigma, such as female survivors of stigma concerning sexual violence (Greiner et al 2014;Verelst et al 2014;Babalola et al 2015;Scott et al 2015;Murray et al 2018a, b;Wachter et al 2018) and male survivors, (Christian et al 2011), and HIV (Newman et al 2012;Musumari and Feldman 2013;Gebremedhin and Tesfamariam 2017;Tshingani et al 2017;Venables et al 2019). Other studies have discussed stigma related to intimate partner violence (Kohli et al 2015;Glass et al 2018), abortion (Casey et al 2019;Steven et al 2019), syphilis (Nkamba et al 2017), fistula (Young-Lin et al 2015) and contraception-use (Muanda et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of infectious diseases and non-communicable diseases is well documented in developed countries, and the intensity of this comorbidity is incomparable in SSA [11]. In RDC Despite low prevalence of HIV infection (1.2% in the general population [12][13][14][15].There are no studies that have assessed cardiovascular risk factors in patients living with HIV before taking ARVs. However, a comparison of the frequency of CVD reported a prevalence of 20%, 17.4% and 16.7% respectively of chronic renal failure, heart failure and stroke in PLWH.…”
Section: Introductionmentioning
confidence: 99%